Current Status of Computing Education in Central Luzon: Basis for Training and Program - Cuison, Lilibeth T.; Abarintos, Erlinda C.; Datu, Neil H.; Dayrit, Roy D.; Juliano, Evelyn S.; Malang, Bernandino P.; Suba, Joey M.; Tamayo, Josan D.; Vergara, Arnold P.; Vicente, Clarissa P. (International Journal of Multidisciplinary: Applied Business and Education Research, 2025)
This study delves into the current status of computing education in Central Luzon, providing a foundational framework for the development of training programs within the Association of Computing Education Deans and Program Heads (ACED.PH). It addresses a critical research problem: the gap between existing institutional capacities and the quality standards outlined in CHED CMO 25 Series of 2015, particularly in areas of faculty research engagement, laboratory management, and organizational commitment. It investigates the challenges of membership and commitment in professional organizations and underscores the importance of effective leadership for organizational sustainability. ACED.PH, previously known as the Council of Deans in Information Technology Education (CDITE) Region 3, seeks to enhance the well-being of deans, program directors, teachers, and students within the Information Technology Education (ITE) field. The study employs a mixed-method approach, combining a descriptive research design and a survey questionnaire technique to comprehensively gather quantitative and qualitative data. Participants include administrators from accredited schools in Central Luzon offering ITE programs. The study utilizes a structured questionnaire with 72 items, evaluating ITE programs in terms of administration, faculty, curriculum, and laboratories. The study revealed that the schools offering ITE Programs in Central Luzon are above requirement as stipulated in the CMO 25 Series 2015. Furthermore, research capability and engagement of the faculty under the program need to be prioritized in the series of training sessions that the association will implement as it is below the requirement stipulated in the mentioned CMO. On the other hand, training on the upkeep of the laboratories and capability building among technical personnel in the school will be communicated to the school administration for them to be given ample skills and knowledge as computers are vital in the teaching-learning process of the ITE students. Lastly, more research collaboration among ITE Deans and Program Chairs is recommended to strengthen the research engagement of both the administration and faculty. The findings revealed the development of a short- and long-term action plan to ensure the sustainability of training and programs for computing education. The research aligns with the minimum standards set by the Commission on Higher Education CMO 25 Series of 2015 and Manual of Regulations for Private Higher Education (MORPHE). Understanding the current state of computing education in Central Luzon is vital for shaping the future of IT education and professional development within the region.